“Isso é coisa pra macho" - a construção de masculinidade nos encontros de motociclistas em Goiânia - Silva, Kleber Lopes da (2016)
This dissertation has as field researched the motorcycling meetings that took place in Paranaíba avenue in the South Sector cepal, in Goiania, from March 2015 to March 2016. These meetings were held on Thursdays, at night, from 18.30. During my writing I bring the production of an ideal biker, ranging from clothing, posture to some physical features such as the use of beard, long hair, tattoos etc. Features that are references in the meetings. Tied to those references, show a certain historical symbolic repertoire and culturally produced about this universe, in large part, by the media and the market. Gender relations in this field, are shown linked to the use of the vest and motorcycle. The woman's subordination process is a study focus, as well as a market positioning of the female body seen as a product by motorcyclists and the motorcycle dealerships. These relations conditional on a look andro and heteronormative. Another consideration and research are part of the territorial processes, the use of the vest as the brand and the body, tattoos and some props that have their restricted uses, as well as representations that categorize and classify the bodies.